CYP83A1 is required for metabolic compatibility of Arabidopsis with the adapted powdery mildew fungus Erysiphe cruciferarum. Issue 4 (6th March 2014) - Weis, Corina; Hildebrandt, Ulrich; Hoffmann, Thomas; Hemetsberger, Christoph; Pfeilmeier, Sebastian; König, Constanze; Schwab, Wilfried; Eichmann, Ruth; Hückelhoven, Ralph
Summary: Aliphatic glucosinolates function in the chemical defense of Capparales. The cytochrome P450 83A1 monooxygenase (CYP83A1) catalyzes the initial conversion of methionine‐derived aldoximes to thiohydroximates in the biosynthesis of glucosinolates, and thus cyp83a1 mutants have reduced levels of aliphatic glucosinolates. Loss of CYP83A1 function leads to dramatically reduced parasitic growth of the biotrophic powdery mildew fungus Erysiphe cruciferarum on Arabidopsis thaliana . The cyp83a1 mutants support less well the germination and appressorium formation of E. cruciferarum on the leaf surface and post‐penetration conidiophore formation by the fungus. By contrast, a myb28‐1 myb29‐1 double mutant, which totally lacks aliphatic glucosinolates, shows a wild‐type level of susceptibility to E. cruciferarum . The cyp83a1 mutants also lack very‐long‐chain aldehydes on their leaf surface. Such aldehydes support appressorium formation by E. cruciferarum in vitro . In addition, when chemically complemented with the C26 aldehyde n ‐hexacosanal, cyp83a1 mutants can again support appressorium formation. The mutants further accumulate 5‐methylthiopentanaldoxime, the potentially toxic substrate of CYP83A1. Loss of powdery mildew susceptibility by cyp83a1 may be explained by a reduced supply of the fungus with inductive signals from the host and an accumulation of potentially fungitoxic metabolites. Abstract : See also the Commentary by Bednarek